Association between waist circumference or weight change after smoking cessation and incidence of cardiovascular disease or all-cause death in Korean adults with type 2 diabetes - Lee, Heajung; Shin, Jaeyong; Choi, Jae Woo (Frontiers in Endocrinology, 2024)
Objective: To investigate the association among smoking cessation, weight or waist circumference change post-cessation, and cardiovascular disease (CVD) or all-cause death among patients with type 2 Diabetes (T2D). Materials and methods: This retrospective cohort study included 32,142 patients with T2D classified according to changes in smoking status, post-cessation weight, and waist circumference. Especially for recent or long-term quitters, participants who changed from current to none/former smoker or from non-smoker to former smoker were defined as recent quitters, and those who changed from former to none/former smoker were defined as long-term quitters. CVD or all-cause death risk was evaluated. Results: A total of 5,845 participants were newly diagnosed with CVD, and 3,723 died during followup. After adjusting for potential confounding factors, compared with current smokers, the hazard ratios (HRs) for CVD were 0.94 (95% confidence interval [CI]: 0.85-1.03), 0.82 (95% CI: 0.74-0.90), and 0.82 (95% CI: 0.75-0.90) for recent quitters, long-term quitters, nonsmokers, respectively; 0.88 (95% CI: 0.78-0.99), 0.68 (95% CI: 0.57-0.81), and 0.82 (95% CI: 0.67-1.00) for long-term quitters with no waist circumference gain, long-term quitters with waist circumference gain of 0.1-5.0 cm, and long-term quitters with waist circumference gain ≥5.0 cm, respectively; and 0.79 (95% CI: 0.71-0.89), 0.85 (95% CI: 0.74-0.98), and 0.84 (95% CI: 0.60-1.17) for long-term quitters with no weight gain, long-term quitters with weight gain of 2-5 kg, and long-term quitters with weight gain ≥5 kg, respectively. Similar associations were observed for all-cause death. Conclusions: Patients with T2D should maintain their weight and waist circumference after long-term smoking cessation to prevent CVD. It is more important for them to maintain weight rather than waist circumference to prevent all-cause death.